Anatomic femorotibial changes associated with tibial plateau leveling osteotomy - Schultz, Jennifer A. (Can Vet J, 2015)
This prospective study evaluated anatomic femorotibial changes utilizing the relationship between the intercondylar notch and the intercondylar eminence following tibial plateau leveling osteotomy (TPLO). We hypothesized that TPLO results in anatomic alteration of the femorotibial joint. Pre- and post-operative computed tomography (CT) scans of cranial cruciate deficient stifle joints treated with TPLO were performed on 25 client-owned dogs. Computed tomography scans were performed at 3 different stifle angles: extension, 135° walking angle, and 90° of flexion. Tibial plateau leveling osteotomy did not result in a significant medial or lateral shift of the intercondylar eminence relative to the intercondylar notch. There was a significant cranial shift of the intercondylar eminence with the stifle in extension following TPLO. In addition, TPLO resulted in a significantly narrowed femorotibial joint space. The biomechanical effects of TPLO and medial meniscal release need to be further defined.